THE EFFECTIVENESS OF LAW ENFORCEMENT AGAINST ONLINE GAMBLING CRIMES IN INDONESIA: A CRIMINAL LAW AND CRIMINOLOGICAL PERSPECTIVE - Kuswardani Kuswardani; Bambang Sukoco (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the effectiveness of law enforcement against online gambling crimes in Indonesia from criminal law and criminological perspectives. The rapid development of information technology has transformed conventional gambling into more complex, anonymous, and transnational digital forms, posing challenges in offender identification and regulatory adaptation. This research employs a normative juridical approach using secondary data from laws, legal doctrines, and academic literature, analyzed qualitatively through a descriptive-analytical method. The findings reveal that law enforcement remains suboptimal despite existing regulations such as the Information and Electronic Transactions Law. Key obstacles include limited institutional capacity, increasingly sophisticated modus operandi, and the transnational nature of the crime. From a criminological perspective, this phenomenon is driven by opportunity structures, ease of technological access, and economic motivations. This study highlights the need for regulatory strengthening, institutional capacity improvement, and integrated legal and criminological approaches.